The experience of foreign countries in conciliation of the parties to a civil dispute: using the example of European countries - Shaimenova , A.B. (Bulletin of the Karaganda University “Law Series”, 2019)
The article studies practical application and development of mediation as one of the types of alternative dispute resolution methods using the example of such European countries as Poland, Germany, Spain, France, as well as England and Wales. The experience of these countries indicates this method effectiveness to a large extent, as well as its positive impact on judicial system. The aim of the study is to analyze mediation regulato-ry practice in foreign countries and civil society’s attitude towards dispute resolution with the help of media-tors. General and scientific and special research methods are used in this work: analysis, synthesis, abstraction, induction and deduction, logical and comparative and legal method. It is noted that the introduc-tion of pre-trial disputes resolution methods in Kazakhstan legal system requires enough time and financial costs, for this reason many contradictions in this area remain unresolved and poorly studied. Scientific inter-pretation of issues of the application of considering method of alternative resolution of dispute seems to be necessary for further development of national law and its institutions. The author came to a conclusion that Alternative Dispute Resolution (ADR) is widely used inEuropean regulatory practice, which has more ad-vantages than the state court proceedings. So, ADR is performed by a non-state body or a private person based on the principles of voluntariness, neutrality, confidentiality, dispositiveness, equality and therefore do not require significant financial costs from contentiousrelation participants. Also, the advantage of ADR is that the latter provide an opportunity not only to eliminate a conflict but to reconcile the opposing parties, and therefore, keep good and business relationships. Despite the fact that ADR methods have a lot in common in different European countries, their role in human rights protection and interaction with jurisdictional protection are very different.